In vitro sperm generation from immature mouse testicular tissue using plasma rich in growth factors - Seyyed Amir Moradian; Mansoureh Movahedin (Stem Cell Research & Therapy)
Abstract Background Culture medium enriched with Knockout serum replacement (KSR) can produce in vitro mouse sperm, but it is inefficient, strain-specific and contains bovine products, which limits its use in the human clinic. The study aimed to optimize the culture medium for testicular tissue by using plasma rich in growth factors (PRGF) as a serum supplement, addressing the limitations of KSR. Methods Immature testicular tissues from NMRI mice were cultured for 14 days to identify the optimal PRGF concentration using histological analysis and tubular integrity scoring. Subsequently, tissues were cultured for 42 days with the optimal PRGF concentration and compared to a control group with 10% KSR, followed by evaluation through histological, tubular integrity, and immunofluorescence assays. Results After 14 days, 5% PRGF media significantly preserved tubule integrity better than 10% and 20% PRGF, performing similarly to 10% KSR. However, after 42 days, the integrity scoring revealed significantly a higher percentage of well-preserved tubules in 5% PRGF compared to 10% KSR. Additionally, only PRGF supported spermatogenesis to the production of flagellated sperm. Real-time PCR analysis revealed that transcript levels of Plzf, Tekt1, and Tnp1 were significantly elevated in 5% PRGF compared to 10% KSR. Immunofluorescence and quantitative analysis confirmed enhanced spermatogenesis progression in 5% PRGF media, with significantly increased numbers of PLZF + spermatogonia, SYCP3 + spermatocytes, ACRBP + spermatids, and Ki67 + proliferating cells per tubule compared to 10% KSR. Moreover, 5% PRGF showed a significantly lower mean fluorescence intensity of the pro-apoptotic marker Bax, with no significant difference in the anti-apoptotic marker Bcl-2 compared to KSR. Conclusions The findings suggest that 5%PRGF is a viable alternative to KSR in mouse testicular tissue cultures, promoting structural integrity and spermatogenesis up to the production of flagellated sperm. The results highlight PRGF’s potential to improve culture media for in vitro sperm production, suggesting promising avenues for future human research. Graphical Abstract